Neurofibromatosis in pediatrics: new early diagnostic parameters. - Becú, I.; Crespi, H.G.; Ledesma, J.L. (European Journal of Pediatric Dermatology, 2018)
80 children with café au lait spots (CALS), independently from their number, were studied; 45 of them reached an accurate diagnosis of neurofibromatosis (NF). Clinical multidisciplinary evaluations, neurologic and orthopedic systematic screenings were performed. With or without NF diagnosis, they turned out to represent a high risk pediatric group, with relevant incapacitating multisystemic pathologies, either neurologic, orthopedic, endocrinologic or others. Among 45 patients with NF, 40 showed severe involvement (34 neurologic, 24 orthopedic, 11 ophthalmologic, 9 endocrinologic and 2 cardiologic); 38 had at least 2 independent from the classical phenotypic features: 38 had positive pregnancy and perinatal background; 39 out of 42 families referred non-NF specific background; 20 out of 40 children evidenced language disorders. Among 35 patients with CALS, 30 showed severe involvement (25 neurologic, 13 orthopedic, 2 ophthalmologic, 9 endocrinologic and 1 cardiologic); 26 had at least 2 independent from the classical phenotypic features; 28 had positive pregnancy and perinatal background; 28 out of 33 families referred non-NF specific background; 14 out of 25 children evidenced language disorders. Phenotype, background and language disorders are useful parameters for an imperious NF early diagnostic score in pediatrics.